Quantum Negotiation - Walch, Karen; Mardyks, Stephan; Schmitz, Joerg (Ascent Audio, 2018)
Quantum Negotiation is a handbook for getting what you need using a mindset and behaviors based on a refreshingly expansive perspective on negotiation. Rather that viewing every negotiation as an antagonistic and combative relationship, this book shows you how to move beyond the traditional pseudo win-win to construct a deal in which all parties get what they need. By exploring who we are as negotiators in the context of social conditioning, this model examines the cognitive, psychological, social, physical, and spiritual aspects of negotiation to help you produce more sustainable, prosperous, and satisfying agreements. We often think of negotiation as taking place in a boardroom, a car dealership, or any other contract-centered situation; in reality, we are negotiating every time we ask for something we need or want. Building more robust negotiation behaviors that resonate beyond the boardroom requires a deep engagement with others and a clear mindset of interdependence. This book helps you shift your perspective and build these important skills through a journey of discovery, reflection, and action.